Retrograde Wiring of Collateral Channels of the Heart in Chronic Total Occlusions: A Systematic Review and Meta-Analysis of Safety, Feasibility, and Incremental Value in Achieving Revascularization. (November 2015) - Khand, Aleem; Patel, Bilal; Palmer, Nicholas; Jones, Julia; Andron, Mohammed; Perry, Raph; Mehrotra, Sanjay; Mitsudo, Kazuaki
Aim: To conduct a systematic review and meta-analysis on retrograde wiring in chronic total occlusions (CTOs) with focus on its safety and feasibility. Methods and Results: We searched publications from 1990 to December 2013 in PubMed, Ovid, EMBASE, and the Cochrane database inserting a number of terms relating to the collateral circulation of the heart in CTOs. A total of 18 case series (n range17-462) with a total of 2280 CTO revascularization attempts fulfilled criteria for a study of retrograde wiring of collateral channels in CTOs. There were no randomized studies comparing a primary antegrade with a primary retrograde approach. Procedural CTO revascularization rates ranged from 67% to 90.6% with a large proportion having previously failed an "antegrade" approach. The septal perforator collaterals and epicardial channels were used in 73.2% (n = 1670) and 21.7% (n = 495) of cases. Although collateral/coronary perforation was not infrequent (n = 90, 5%), serious acute complications were uncommon; in the combined population 18 cases of cardiac tamponade (0.8%) and 3 deaths (0.1%). Septal perforating wiring (79.3%) was significantly more likely to be successful compared to epicardial coronary artery wiring (72.5%) when chosen by the operator as a route of retrograde access to the CTO body (relative risk 1.11 [95% confidence interval: 1.02-1.20; P = .013]). Conclusion: Successful retrograde wiring of collateral channels in selected patients undertaken by "CTO dedicated" operators can significantly enhance the chances of revascularization of complex CTOs with a low risk of acute serious complications. Septal perforator channels are significantly more likely to be successfully retrogradely wired compared to epicardial vessels when either is selected, by reference to their anatomical suitability by the operator, as a route of access.